Intraamniotic Inflammation in Women with Preterm Prelabor Rupture of Membranes - Musilova, Ivana; Kutová, Radka; Pliskova, Lenka; Stepan, Martin; Menon, Ramkumar; Jacobsson, Bo; Kacerovsky, Marian (PloS one, 2015)
OBJECTIVE: To characterize subgroups of preterm prelabor rupture of membranes (PPROM) and short-term neonatal outcomes based on the presence and absence of intraamniotic inflammation (IAI) and/or microbial invasion of the amniotic cavity (MIAC). METHODS: One hundred and sixty-six Caucasian women with singleton pregnancies were included in this study. Amniotic fluid samples were obtained by transabdominal amniocentesis (n=166) and were assayed for interleukin-6 levels by a lateral flow immunoassay. The presence of Ureaplasma species, Mycoplasma hominis, Chlamydia trachomatis, and 16S rRNA was evaluated in the amniotic fluid. IAI was defined as amniotic fluid IL-6 values, measured by a point of care test, higher than 745 pg/mL. RESULTS: Microbial-associated IAI (IAI with MIAC) and sterile intraamniotic inflammation (IAI alone) were found in 21% and 4%, respectively, of women with PPROM. Women with microbial-associated IAI had higher microbial loads of Ureaplasma species in the amniotic fluid than women with MIAC alone. No differences in the short-term neonatal morbidity with respect to the presence of microbial-associated IAI, sterile IAI and MIAC alone were found after adjusting for the gestational age at delivery in women with PPROM. CONCLUSIONS: Microbial-associated but not sterile intraamniotic inflammation is common in Caucasian women with PPROM. The gestational age at delivery but not the presence of inflammation affects the short-term neonatal morbidity of newborns from PPROM pregnancies.
Keywords: dospělí; chorioamnionitida; Chorioamnionitis; Female; Prevalence; předčasný odtok plodové vody; novorozenec; Adult; ženské pohlaví; RNA, Ribosomal, 16S; lidé; Infant, Newborn; těhotenství; Interleukin-6; Fetal Membranes, Premature Rupture; prevalence; Amniotic Fluid; plodová voda; interleukin-6; Pregnancy; RNA ribozomální 16S; Humans